Hubungan kepimpinan instruksional ketua panitia dan komitmen guru di sekolah rendah - Noazli, Abu Bakar (2009)
This study is conducted to find the relationship between instructional leadership of the subject panel heads and the teachers' commitment in the primary school in Tambun Tulang Area. The study is focusing on several factors such as gender and academic qualification in ascertain whether there are differences in instructional leadership implemented by the heads of panel against the commitment of the teacher. Further, the study will look into functions of instructional leaderships in terms of drafting and clarifying the objectives, supervise, coordinate and evaluate the teaching of curriculum, support and encouraging staff development by the panels head and its relationship with teachers' commitment. The data of this study is collected through questionnaires on 140 teachers. For this purpose, the questionnaire, based on "Principal Instructional Management Rating Scale (PIMRS), is used to determine the level of instructional leadership of the panel heads. On teachers' commitment, "Commitment to School (CSS) and Organisational Commitment Questionnaires (OCQ)" based-typed questionnaire is being used. Questionnaires on instructional leadership and teachers' commitment consists of 31 and 28 question items respectively, are using Likert Scale format. T-test is used to find difference between gender and academic qualification and instructional leadership of the panel heads. Pearson R test is used to test the correlation between the functions of instructional leadership and the commitment if the teachers. In brief, we found that there are no significant differences between the gender and academic qualification of the respondents towards the commitments of the teachers and the instructional leadership of the panel heads. However, there are significant relationship between instructional leadership head of panels with the teachers' commitment